Comparative study of the technique Marshall-Marchetti-Krantz and Burch technique Archbishop Loayza Hospital - Siu, Alejandro (2015)
These two techniques that bear the names of their authors, are the best known of all suprapubic colposuspension techniques that are used more frequently here and elsewhere in the mundo1-5; even the Burch technique has been used in the laparoscópica6,7 surgery. This study aims at comparing both conventional open surgery for assessing the existence of any advantage of one technique over the other in urinary incontinence (SUI).